Cancer Risk Levels for Sediment- and Soil-Bound Polycyclic Aromatic Hydrocarbons in Coastal Areas of South Korea - Roy, Debananda; Jung, Woosik; Kim, Jayun; Lee, Minjoo; Park, Joonhong (Frontiers in Environmental Science, 2021)
The increasing cancer risk (CR) due to sediment- and soil-bound polycyclic aromatic hydrocarbons (PAHs) is a major threat to public health. The CR of sediment- and soil-bound carcinogenic PAHs was estimated for the first time in coastal and residential areas near an industrial zone in Korea. Monte Carlo probabilistic simulations and sensitivity tests were conducted to calculate the CR and to identify the most sensitive parameters. The CR was found to be highest in the coastal areas of Korea. Ulsan, which is located on the southeastern coast of Korea, was classified as a high cancer risk zone according to United States Environmental Protection Agency standards, while the western coast and Mohang Harbor were classified as moderate cancer risk zones. Fish consumption was identified as the main contributor (94–99%) to the total risk levels in the coastal areas. The biota-to-sediment accumulation factor (43–76%) and PAH levels (8–44%) in sediment were identified as the parameters that were most sensitive to the CR. In the residential area, the CR was found to be within the range of 10-6 to 10-4, which categorized it as a low cancer risk zone. Furthermore, the CR for residents in the industrial area was estimated to be 12 and 5 times higher than that for residents in the rural and urban areas, respectively. The exposure duration (55–85%) and skin adherence factor for soil (35–42%) were identified as the most sensitive parameters for the overall CR in the residential area. Korea generally has high fish and seafood consumption, which has been recognized as the most significant exposure route for CR in coastal areas. Thus, the consumption of fish and seafood from coastal areas, especially those near Ulsan, might be responsible for the increasing number of cancer patients in Korea.